If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3(3) + 6 = 0 Multiply -3 * 3 -9 + 6 = 0 Combine like terms: -9 + 6 = -3 -3 = 0 Solving -3 = 0 Couldn't find a variable to solve for. This equation is invalid, the left and right sides are not equal, therefore there is no solution.
| 0.504=0.9*w*0.7 | | x-3(1-3)=47-x | | 6a+3b+-8a+5ab+-7b= | | 12x+4x+5=5x+8+3x | | 5.3y+0.5=3.1y-5 | | x+14=20x | | 60=2i+2(14) | | 13=1-7x | | 4.8x+3.1=2.3x+10.1 | | I-12=v | | 55=2y+15 | | 6a+3b-8a+5ab-7b= | | (0.15x+x^2)/(4-4x+x^2) | | 5x-8(x+5)=3-3x | | 139-y=283 | | .45x^2+11.7x=101.4 | | -(2x+4)-x+2-3x= | | x^2+20x=200 | | 4=m+17 | | x^2-20x=200 | | 5(x+5)=32 | | (6k-4)(5k-2)= | | p-45=-20 | | 12x-4=8x+2 | | x+11.3=-5.3 | | (28a+4)/((7a+1)*(7a-1)) | | x^2+13x+28=0 | | 5n+3=24 | | x/0.22=0.6/0.33 | | 3x-91=x+3 | | (xlny+xy)dx+(ylnx+xy)dy=0 | | 5/11-x=35 |